(3cJGH GdSeGYs - (3GHf GdbjSQGfj , eMeO Hf WGgQ Hf eMeO GdebOSj, CHh GdaVd,J (B507 (3g` s
(3ChdgG (B:s
(3jHOC Hbhdg aGdPjf BefhG Hg hYRQhg hfUQhg s
(3BNQgG (B:s
(3hjSJf HSfI GdUMGHI hGdJGHjYf CFI GdeSdejf Efg LhGO cQje BNQ cJGH GdSeGY s
(3GdfSNI HgG MhGTs
(3jdi cJGH GdSeGY RjGOGJ Yf CHj GdbGSe GdRLGLi hZjQg ai GdSeGY jdjgG JbjjOGJ HNW GdYdGeI eMeO Hf LYaQ GdcJGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B171 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B98s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdTGaYjs